Proportion of Type 2 Diabetes Mellitus Patients with Hypoglycemia - Baber Ali, Muhammad Umair Sarwar, Sarah Hameed, Junaid Bashir, Syed Imad Hussain, Asma Ashraf, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this particular study is to examine the incidence of hypoglycemia in people who have diabetes type 2. Study Design: Cross-sectional Place and Duration: In the department of Medicine/ Endocrinology of Allied Hospital, Faisalabad for the duration from November 2021 to April 2022. Methods: Overall, 86 patients of both sexes were presented with type-2 diabetes mellitus. Among the patients were those as young as 18 and as old as 65. Before having their demographic information collected, participants signed a consent form indicating they had read the information and understood its importance. Whipple's triad questionnaire data were used to record the occurrence of hypoglycemia. Hypoglycemia symptoms were also documented. All data were analysed with SPSS 20.0. Results: All instances shared the most typical symptoms of dizziness, weakness, and sweating. In all cases, metformin was the most often used medication, followed by glynase and insulin. Among all, 43 (50%) patients diagnosed with hypoglycemia and majority were females. Eight of the 43 cases of hypoglycemia were extremely severe, seventeen were moderate, and eighteen were mild. Conclusion: The majority of the patients in this study were women from rural areas who were diagnosed with type 2 diabetes. Due to its prevalence, primary care physicians should inquire about hypoglycemia in all patients with diabetes. It is also important to teach patients how to recognise the signs of hypoglycemia and how to report them so that their dosage can be adjusted and further attacks can be prevented. Keywords: Glynase, Dizziness, Hypoglycemia, Type 2-diabetes Mellitus, Hypoglycemia